Association of physical activity and motor skills with academic performance in high school students of Hayatabad, Peshawar: A cross-sectional study - Uzair Ahmad; Babar Ali; Seema Gul; Ikram Ali (Journal Riphah College of Rehabilitation Sciences)
Background: Regular physical activity has a positive impact on brain function, improves perception, and significantly influences academic achievement.